The Diversity of Nepenthes spp. in Multipurpose Forest, Green Campus Area of University of Palangka Raya, Central Kalimantan, Indonesia - Elga Araina; Sugeng Mashabhi; Chaidir Adam; Ririn Fahrina (Future Science, 2022)
The Multipurpose Forest Area located at the University of Palangka Raya is a peatland forest area in which there are many types of plants, one of which is the pitcher plant (Nepenthes spp.). Nepenthes is a genus of insectivorous plant and generally lives in nutrient-poor soils. This study aimed to determine the diversity of pitcher plants (Nepenthes spp.) in the Multipurpose Forest area of ??the University of Palangka Raya. This research is descriptive - quantitative research using 10 box plots with a size of 5×5m for data collection. The results showed that 17 species of Nepenthes were found at the study site with a diversity index of 2.41 in the medium category. The species found included N. gracilis, N. tobaica, N. distillatoria, N. gracilis Red, N. reinwardtiana, N. mirabillis, N. raflesiana, N. maxima, N. smilesi, N. devin, N. domei, N. gracilis Korth, N. harsuta, N. hamiguitanensis, N. vogelii, N. Khasiana, and N. Alata. N. gracillis Red is the most dominant species with 123 individuals found and has a dominance index value (D) of 27.21%.